Al-Hanin fi Muwashshahat “Jadaka al-Ghaythu” li-Lisan al-Din ibn al-Khatib: Dirasah Dalaliyyah: Longing in Lisan al-Din ibn al-Khatib’s Muwashshaha “Jadaka al-Ghayth”: A Semantic Study - Ikram Azmi; Fahmi Sofyan; Anshar Zulhelmi (An-Nahdah Al-'Arabiyah, 2026)
Although the muwashshaḥ Jādaka al-Ghayth by Lisān al-Dīn Ibn al-Khaṭīb has been extensively studied from literary, historical, and phonological perspectives, its semantic construction of ḥanīn (longing) through Ahmad Mukhtar 'Umar's semantic theory remains largely unexamined. This study analyzes how the meaning of ḥanīn is constructed in the muwashshaḥ using Ahmad Mukhtar 'Umar's semantic framework. Employing a qualitative descriptive method, the study examines eight selected verses containing explicit or implicit lexical markers of ḥanīn, classified according to five semantic categories: basic, additional, Affective, suggestive, and stylistic meaning. The findings show that ḥanīn is not merely an emotional expression but a composite semantic structure built through the interrelation of four functional dimensions: historical-spatial reference, natural symbolism, psychological affect, and rhetorical strategy. This relational structure reconstructs the Andalusian past as an idealized space set against the poem's experience of loss. The study demonstrates the applicability of Ahmad Mukhtar 'Umar's semantic theory to classical Arabic poetry and offers a systematic semantic model for interpreting ḥanīn, with implications for both semantic scholarship and the teaching of critical literary reading.   على الرغم من أن موشحة "جادك الغيث" للسان الدين بن الخطيب قد حظيت بدراسات عديدة من الجوانب الأدبية والتاريخية والصوتية، فإن بنيتها الدلالية للحنين في ضوء نظرية أحمد مختار عمر لم تحظَ بدراسة متخصصة. تحلل هذه الدراسة كيفية تشكل دلالة الحنين في هذه الموشحة اعتمادًا على نظرية أحمد مختار عمر في علم الدلالة. واعتمدت الدراسة المنهج الوصفي النوعي، وتناولت ثمانية أبيات مختارة تتضمن مؤشرات لفظية صريحة أو ضمنية على الحنين، صُنِّفت وفق أنواع المعنى الخمسة: الأساسي، والإضافي، والنفسي، والإيحائي، والأسلوبي. وأظهرت النتائج أن الحنين لا يتجلى بوصفه تعبيرًا عاطفيًا مجردًا، بل يتشكل بوصفه بنية دلالية مركبة تنشأ من تفاعل أربعة أبعاد وظيفية: المرجعية التاريخية-المكانية، والرمزية الطبيعية، والانفعال النفسي، والاستراتيجية البلاغية. وتعيد هذه البنية العلائقية بناء الماضي الأندلسي بوصفه فضاءً مثاليًا في مقابل تجربة الفقد التي يعكسها النص الشعري. وتبرز الدراسة فاعلية نظرية أحمد مختار عمر في تحليل الشعر العربي الكلاسيكي، وتسهم بنموذج تفسيري دلالي منهجي لمفهوم الحنين، بما له من انعكاسات على الدراسات الدلالية وعلى تعليم القراءة النقدية للنصوص الأدبية.   Meskipun muwashshah Jādaka al-Ghayth karya Lisān al-Dīn Ibn al-Khaṭīb telah banyak dikaji dari perspektif sastra, sejarah, dan fonologi, konstruksi semantik ḥanīn (kerinduan) berdasarkan teori semantik Ahmad Mukhtar Umar masih jarang diteliti secara khusus. Penelitian ini menganalisis bagaimana makna ḥanīn dibangun dalam muwashshah tersebut menggunakan kerangka semantik Ahmad Mukhtar Umar. Dengan metode deskriptif kualitatif, penelitian ini mengkaji delapan bait terpilih yang memuat penanda leksikal ḥanīn secara eksplisit maupun implisit, yang diklasifikasikan berdasarkan lima kategori makna: makna dasar, tambahan, psikologis, sugestif, dan stilistika. Hasil penelitian menunjukkan bahwa ḥanīn tidak sekadar dimaknai sebagai ungkapan emosional, melainkan sebagai struktur semantik majemuk yang terbentuk melalui relasi empat dimensi fungsional: referensi historis-spasial, simbol alam, afeksi psikologis, dan strategi retoris. Struktur relasional ini membangun kembali citra masa lalu Andalusia sebagai ruang yang diidealkan, dikontraskan dengan pengalaman kehilangan yang tercermin dalam puisi. Penelitian ini membuktikan penerapan teori semantik Ahmad Mukhtar Umar pada puisi Arab klasik serta menyumbangkan model interpretasi semantik yang sistematis terhadap ḥanīn, dengan implikasi bagi kajian semantik maupun pengajaran pembacaan sastra secara kritis.